Generative AI as a Dynamic Marketing Capability: Mechanisms of Strategic Reconfiguration - Edi Firdaus (Manexia: Journal of Business, Management, and Creative Economy, 2025)
The rapid diffusion of Generative Artificial Intelligence (GenAI) represents a structural inflection point in the evolution of marketing capabilities. While prior research has predominantly examined AI as a performance-enhancing tool, limited attention has been devoted to understanding how generative systems reshape the microfoundations of strategic marketing processes. This study conceptualizes GenAI as a dynamic marketing capability rather than a technological artefact. Drawing on dynamic capabilities theory, marketing capability research, and organizational learning perspectives, we develop a mechanism-based framework explaining how GenAI reconfigures marketing capabilities through three interrelated processes: cognitive amplification, creative recomposition, and decision authority redistribution. We further specify boundary conditions—task complexity, market dynamism, brand positioning, and governance maturity—that moderate whether generative integration enhances adaptive capacity or produces capability erosion. By extending dynamic capabilities theory into probabilistic technological environments, this study advances a socio-technical understanding of marketing capability evolution and clarifies the long-term strategic implications of AI-enabled marketing transformation. The analysis contributes to ongoing debates on capability sustainability, organizational learning, and digital governance in increasingly algorithmic organizational contexts.